Analisis Efektivitas dan Kontribusi Pajak Bumi dan Bangunan terhadap Pendapatan Asli Daerah - Achmad Rifa’i; Ismunawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effectiveness and contribution of the Rural and Urban Land and Building Tax (PBB-P2) to the Local Own-Source Revenue (PAD) of Boyolali Regency. The research employed a descriptive quantitative method using secondary data from the Boyolali Regional Financial Agency for the period 2019–2023, including data on targets, realizations, and tax contribute. The results show that PBB-P2 collection in Boyolali was highly effective, with an average effectiveness rate of 101.79%, indicating that revenue targets were successfully achieved. However, the contribution of PBB-P2 to PAD remained relatively low at an average of 9.18%, suggesting that despite its effectiveness, this tax has not yet become a major contributor to local fiscal independence. These findings highlight the need for optimization through updated tax object data management and increased taxpayer awareness to enhance future PBB-P2 performance.